2000
DOI: 10.1111/1467-8489.00123
|View full text |Cite
|
Sign up to set email alerts
|

The application of trade and growth theories to agriculture: a survey

Abstract: This article reviews a broad range of theoretical concepts available to explain international trade in agricultural and food products. For many years agricultural trade analyses were largely based on traditional perceptions of comparative advantage following neoclassical theory. Observations of agricultural trade suggest, however, that concepts from modern trade and growth theories are increasingly relevant. This survey demonstrates that many opportunities exist for applying these new theories to the modern fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…In the long run, the sector that is thought to be successful performs less well than partial competitiveness studies predict. The better performing sectors can pay an additional ''rent'' for the production factors (labor and/or capital) and outperform the high, but domestically lower performing sectors (van Berkum & van Meijl, 2000).…”
Section: Competitiveness Indicatorsmentioning
confidence: 99%
“…In the long run, the sector that is thought to be successful performs less well than partial competitiveness studies predict. The better performing sectors can pay an additional ''rent'' for the production factors (labor and/or capital) and outperform the high, but domestically lower performing sectors (van Berkum & van Meijl, 2000).…”
Section: Competitiveness Indicatorsmentioning
confidence: 99%
“…Trade in agricultural goods has traditionally been explained by comparative advantages and neoclassical trade theory. However, explanations of international trade in agricultural products through new trade theory are increasingly relevant (van Berkum and van Meijl 2000). McCorrison and Sheldon (1991) have shown that US-European intraindustry trade in processed agricultural products was of growing importance already in the period 1977-1986.…”
Section: Introductionmentioning
confidence: 99%
“…The landscape of trade in agriculture has been changing across the globe. However, more attention is given to the trade in processed food and agricultural products than trade in raw agricultural products (Berkum and Meij, 2000) which form the bulk of poor countries' markets.…”
mentioning
confidence: 99%
“…Some studies have attempted to link trade theories to food and agriculture in recent times (Abbott and Kallio, 1996;Berkum and Meij, 2000;Josling et al, 2010;Pokriv ák, Ciaian and Kancs, 2011;Campi and Duenas, 2014), however, most of these studies concentrated mainly in processed food and agricultural products in the developed countries or regional trading blocs such as the United States of America (USA) and the European Union (EU). To the best of my knowledge, these studies have not given much attention to trade theories with reference to trade in raw agricultural products of Sub-Saharan Africa (SSA), thus the importance of this study.…”
mentioning
confidence: 99%